PENGGUNAAN GADGET DENGAN KECERDASAN EMOSIONAL ANAK USIA SEKOLAH - Sari, Etika Purnama (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
The effect of gadget use on children is one of mental problems. Children who often use gadgets are not able to control themselves well from the tendency to play their gadgets so that emotions will increase when disturbed by others. The purpose of this study is to analyze the relationship of gadget use with the child's emotional intelligence. The design of the research is correlational. This research was conducted in February 2020. The population in this study was school-age children (9-12 years old) at SDN Simokerto VI/139 Surabaya numbered 400 people, and the sample number was 200 people. Sampling technique in this study is simple random sampling. Data collection using questionnaires. Data analysis using person chi square statistical test. The results were obtained by most (47.5%) respondents who use gadgets that â‰¤ 2 hours have high emotional intelligence, and the result of p value = 0.000 with Î± = 0.05 (p value<Î±) which means the relationship between the use of gadgets and emotional intelligence of the child. This is because the reasonable duration of playing gadgets will not create addiction so that emotions remain stable when there is a disturbance. It is expected that respondents maintain and limit the duration of using gadgets so as not to experience addiction a maximum of 2 hours in a day and emotional intelligence does not decrease.